Violation of Judicial Ethics as a Basis Responsibility of Judge - Овчаренко, О. М. (Theory and practice of jurisprudence, 2016)
The author analyzes ethical standards of judicial profession. International legal acts regulating the issues of judicial ethics and relevant international experience are reviewed. Provisions of the Code of Judicial Ethics, approved by the XIth Congress of Judges on February 22, 2013. The mechanism of subjecting judges to responsibility for violation of moral and ethical principles of judicial conduct are studied.